Rural development and decline in a medieval manor during the eleventh to fourteenth centuries: new insights from excavations at Graven Hill, Oxfordshire - Allen, Martyn G; Teague, Steve (Medieval Settlement Research, 2025)
The discovery and excavation of a medieval rural settlement at Graven Hill has enriched our understanding of the history of the Oxfordshire landscape. A new farmstead was established in the late eleventh century and developed in the thirteenth century with a series of masonry buildings apparently arranged around a central courtyard, linked via a road to the deserted medieval village at Wretchwick. The site is significant for its well-preserved structural foundations and a considerable number of artefacts, including one of the largest medieval pottery assemblages known from rural Oxfordshire. The farmstead was abandoned around the same time as the village in the mid-fourteenth century, perhaps as a result of the Black Death. The land was subsequently used for agriculture until the development of MoD Bicester in the 1940s.